Off the menu Asian and Asian north American women's religion & theology - Brock, Rita Nakashima; Jung Ha Kim; Kwok Pui-Lan; Seung Ai Yang (Louisville The Westminister Press, 2007)
Asian American Christianity is one of the fastest-growing forms of American Christianity, and it has already proven to be one of the richest and most innovative movements in North American religion.
Keywords: Theology - Feminist. Asian American women -- Religion. Feminist theology. Women -- Religious life -- Asia. Women -- Religious life. Asia